Análise molecular e fenotípica do Acinetobacter baumannii em dois hospitais de Cuiabá, Mato Grosso, 2011-2015 : perfil de resistência e relação com desfecho clínico - Azevedo, Francisco Kennedy Scofoni Faleiros de (2018)
Acinetobacter baumannii is a major cause of multidrug-resistant (MDR) nosocomial infections. We investigated the prevalence of MDR A. baumannii at two hospitals in a city of Central Brazil by analyzing the phenotype and molecular characteristics of isolates recovered from patients. The isolates were identified and antimicrobial susceptibility was evaluated using Bact/Alert 3D and Vitek2 method. Patients’ clinical data were obtained from medical records. Genes associated with resistance to carbapenems were analyzed by multilocus sequence typing; clinical and bacteriological variables were analyzed by descriptive statistics, and logistic models were generated to adjust the associations. Most of the 87 A. baumannii isolates analyzed were from patients in intensive care. The mortality rate was 43.7%. The majority of isolates were MDR; 80 (91.9%) were resistant to imipenem and 86 were susceptible to colistin (98.8%). The blaOXA-23 gene (78.2%) and its upstream insertion ISAba1 (55.2%) were predominant, followed by blaOXA-24 (55.2%) and blaOXA-143 (28.7%); and blaOXA-23 gene and ISAba1 were independently associated with resistance to imipenem (P < 0.05). Thirteen different sequence types (STs) were identified among 35 isolates; ST1, ST162, and ST730 were the most common, and four new STs were identified. The isolates were grouped into five clonal complexes (CC1, CC15, CC79, CC108, and CC162) plus a singleton using eBurst. Respiratory infection, age > 60 years, and use of noradrenaline were factors associated with fatality, and ST730 (CC79) was associated with higher mortality rate (P < 0.05). While ST162 (CC162) was associated with a higher chance of survival (P < 0.05).